Estimation of consumers’ purchase intention through Electronic Word of Mouth: A partial least square-structural equation modeling approach (KASBIT Business Journal, 2021)
The advancement of technology has boosted marketing activities through different electronic mediums. Electronic word of mouth (e-WOM) is one of the main mediums of marketing in recent times. The potential of e-WOM communications has increased due to social media interactions. With e-WOM companies are engaging consumers and driving the sales. From company perspectives, information characteristics, consumer motives, technological advancements are keys that engage consumers and drive purchase intention. Therefore, this study has developed a framework based on the Elaboration Likelihood Model (ELM) to assess the impact of e-WOM on consumer engagement and purchase intention. This model was assessed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings of the study revealed that the proposed theoretical model based on ELM lenses has high predictive power to depict purchase intention in e-commerce and suggests that information credibility, self-enhancement, and e-WOM engagement are vital factors that affect the purchase intention in e-commerce. The results provide valuable implications to the practitioners and managers of online companies.
Keywords: Information Quality, Information credibility, Innovativeness, e-WOM engagement, Purchase Intention; Information Quality; Information credibility